ChemInform Abstract: Non‐collinear Magnetic Structures of TbCoO3 and DyCoO3. Issue 17 (28th April 2014) - Knizek, K.; Jirak, Z.; Novak, P.; de la Cruz, Clarina
Abstract The crystal and magnetic structures of the title orthoperovskites are revisited by powder neutron diffraction at selected temperatures between 0.25 and 150 K.